Evaluation of the Ophthalmotoxic Effect of Quantum Dots InP/ZnSe/ZnS 660 and Bioconjugates Based on Them in Terms of the Prospects for the Treatment of Resistant Endophthalmitis. Experimental Research. Part 2 (Stage 1) - V. O. Ponomarev; V. N. Kazaykin; A. V. Lizunov; A. S. Vokhmintsev; I. A. Vainshtein; S. V. Dezhurov; V. V. Marysheva (Oftalʹmologiâ)
The problem of chemo/antibiotic resistance in modern medicine remains relevant today. The sensitivity of microorganisms (MO) determines the range of drugs used, which ultimately affects the effectiveness of treatment and the prognosis for the patient. However, taking into account the adaptation process of individual strains of MO, the uncontrolled use of antibiotics will inevitably lead to the maintenance of the so-called crisis of antibiotic resistance throughout the world, as well as the formation of a vicious circle that reduces the functional and anatomical outcomes of the treatment of any inflammatory diseases, including ophthalmological ones. This article presents the process of experimental creation and certification, assessment of the physicochemical properties of quantum dots, as well as biological nanoconjugates as an option for overcoming the antibiotic resistance of certain strains of microorganisms in the treatment of infectious and inflammatory pathology in ophthalmology, in particular endophthalmitis. Also, an animal model has demonstrated the safety of using InP / ZnSe / ZnS 660 quantum dot solutions for intravitreal administration in pure form and in combination with antibiotics.